أثر الملكية الإدارية في القيمة السوقية للشركات المدرجة في سوق دمشق للأوراق المالية (دراسة اختبارية باستخدام Tobin’s Q) - نادر, نهاد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى اختبار أثر تطبيق مبادئ الحوكمة المتعلقة بالملكية الإدارية للشركات المدرجة في سوق دمشق للأوراق المالية, شملت عينة الدراسة 24 شركة موزعة على خمسة قطاعات هي: المصارف والتأمين والصناعة والزراعة والخدمات خلال الفترة من عام2009-2014 , واستخدمت أسلوب الانحدار المتعدد في اختبار الفرضيات, وتضمنت المتغيرات المدروسة القيمة السوقية مقاسة حسب توبين كيو Tobin’s Q كمتغير تابع وكل من ملكية الرئيس التنفيذي, حجم مجلس الإدارة, ملكية مجلس الإدارة, استقلالية مجلس الإدارة كمتغيرات مستقلة وحجم الشركة ونسبة المديونية ونوع القطاع كمتغيرات ثانوية. كانت أبرز نتائج الدراسة أن الشركات المدرجة في سوق دمشق للأوراق المالية تلتزم بقواعد الحوكمة لا سيما المتعلقة بالملكية الإدارية منها, التي تؤثر في زيادة القيمة السوقية للشركات ممايشجع المستثمرين على الاستثمار فيها. The study aimed to test the impact of application the principles of corporate governance relating to administrative ownership for listed companies on Damascus Securities Exchange, The study sample included of 24 companies spread over five sectors banking, insurance, industry, agriculture and services during the period from 2009 to 2014, and used multiple regression to test hypotheses. The Variables studied included market value as measured by Tobin's Q-dependent variable and all of the ownership of CEO, board size, ownership of the Board of Directors, the independence of the Board of Directors as independent variables and the size of the company and the proportion of debt and the type of sectors a secondary variables. The most significant results of the study that listed companies in Damascus Securities Exchange abide by the rules of governance, particularly relating to administrative ownership of them. Affecting the increased market value of the companies, which encourages investors to invest in them.